Nilai Moral dalam Kumpulan Cerpen Lelaki di Kota Gawai sebagai Bahan Ajar Pembelajaran Sastra di SMP - Chadhiroh, Nurul; Baihaqi, Imam; Hapsari, Theresia Pinaka Ratna Ning (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
This research is motivated by the existence of moral values ​​contained in the collection of short stories of Men in the City of Gawai and the phenomenon of adolescent moral decline in Indonesia. The objectives of this study are (1) to describe the moral values ​​in a collection of short stories for men in the city of Gawai. (2) Produce teaching materials for learning literature in junior high schools that are developed from moral values ​​in the collection of short stories for Men in the City of Gawai. This research design uses descriptive qualitative research. The subject of this research is the moral value of a collection of short stories entitled Men in the City of Gawai by Kholis Kurnia wati et al. The data used are excerpts of sentences and paragraphs containing moral values ​​in a collection of short stories, while the source of data is obtained from a collection of short stories by Kholis Kurnia Wati et al entitled Men in the City of Gawai. Methods and techniques of data collection in this study is the method of reading with a note-taking technique. The method and analysis technique used is descriptive analysis method. The results of this research collection of short stories of Men in Gawai City contain the moral value of human relations with God, human relations with themselves, human relations with fellow humans. The moral value of a collection of short stories for Men in the City of Gawai can be formulated as teaching materials in the form of handouts of review texts for class VIII in junior high school at KD 3.11 and KD 4.11.